Decolorization of Artificial Waste Remazol Black B using Electrogenerated Reactive Spesies - Didik Setiyo Widodo; Linda Suyati; Gunawan Gunawan; Abdul Haris (Jurnal Kimia Sains dan Aplikasi, 2018)
Electrolysis method (electrodecolorization) coupled with ●OH radicals and chlorine generation has been performed in decolorizing of artificial waste of remazol black B (reactive black 5). The electrodecolorization as one of advanced oxidation process (AOP) shows its determinant potential in overcoming environmental problems due to dye contained waste as well as its green in desaign and efficiency. The project aim was to decolorize the RBB solution completely and effectively. The mission was completed by designing decolorizing reactor working with electrolytic system in tandem with electrogeneration of reactive species from HCl and NaCl electrolyte. Lead oxide, PbO2 was choosen as anode. The efficiency of decolorization process was comparated with those of Na2SO4 as electrolyte. Data of UV-Vis spectrometry, atomic absorption spectrophotometry and COD showed that the performance of electrolysis design was significantly enhanced with the reactive species generation process. Electrolysis of 100 mL sample of 200 mgL-1 RBB with reactive species generation was rearched almost two-fold faster in decolorizing the dye solution rather than in Na2SO4 one. The design rearchs more than 99 % in decoloriziation percentages, reducing COD more than 96 % indicating the potential and effectiveness of electroremediation process.